THE DIRECTIONS FOR IMPROVING THE PREPARATION OF SPECIALISTS WITH THE USAGE OF NATIONAL VALUES AT COLLEGES - Jiyankulova R. Kh (International Journal of Innovations in Engineering Research and Technology, 2021)
The article deals with the issue of improving the teaching and methodological support of future specialists in vocational preparing using national values.